Pengaruh Penambahan Kadar Gula Pasir pada Lem Besi Tipe Epoxy terhadap Tegangan Geser Sambungan - Itang Jaelani; Daryono Daryono; Mohammad Jufri (Universitas Muhammadiyah Sidoarjo, 2018)
This research concerned on glueing by adding sugar variation toward metal shear strength tested with tensile test. Shear strength test was conducted as method of this research with tensile test tool where variation of additional suggar is respectively 1 gr, 2 gr, 3 gr, and 4 gr with 3 specimens for each variation. Result of testing shows that the highest value of shear strength is 0.69 kg/mm2 on variation of 1 gr additional sugar. Whereas, 2 gr additional sugar variation resulted the highest shear stress of 0.30 on specimen no. 2. Meanwhile, on 3 gr variation, the highest value is 0.821 kg/mm2 on specimen no. 3. The last variation of 4 gr additional sugar has the highest value on 0.074 for specimen no. 2. It confirms that adding powder on epoxy glue will increase displacement or additional length during testing process. Yet, the highest displacement occur in 3 gr additional sugar variation. It is due to the additional sugar of 3 gr made epoxy dense and less stiff compare with 1 gr, 2 gr, and 4 gr additional sugar. It is as depicted by Table 4.2 on 4 gr variation for shear stress and tensile stress.